Effect of Lutein in the expression of PPARα and LDLR in hypercholesterolemic male Wistar Rats - K., Soundarya Priyadharsini; P., Nirmala; P., Ashok Kumar; T., Krishna Prasad (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hyperlipidemia is a well known risk factor for cardiovascular disease, especially atherosclerotic coronary artery disease. Peroxisome proliferator activated receptor α (PPARα), a member of this nuclear receptor family, has emerged as an important player in this scenario, with evidence supporting a central co-ordinated role in the regulation of fatty acid oxidation, lipid and lipoprotein metabolism and inflammatory and vascular responses, all of which would be predicted to reduce atherosclerotic risk. The low-density lipoprotein (LDL) receptor (LDLR) is the primary pathway for removal of cholesterol from the circulation, and its activity is meticulously governed by intracellular cholesterol levels. Hence in this study we investigated the effect of Lutein on PPARα and LDLR expression in liver of wistar rats. Methods: Male Wistar rats were divided into 6 groups of 6 each. Group I served as control. Group II III, IV, V and VI rats were received high cholesterol diet. Group III was treated with Atorvastatin 5mg/kg. Group IV, V and VI rats were treated with 25mg/kg, 50mg/kg and 100mg/kg of Lutein. After 16 weeks, liver tissue samples were collected from all the groups of animals to evaluate the expression of PPARα and LDLR. Results: The expression of Peroxisome proliferator activated receptor α and low-density lipoprotein (LDL) receptor (LDLR) was significantly increased in Lutein treated hypercholesterolemic male wistar rats. Conclusions: The results of this study indicate that Lutein activates LDL receptor and PPARα in hypercholesterolemic male wistar rats.